Big Tech, the Platform Economy and the European Digital Markets - Volker Brühl (Intereconomics, 2023)
Digital platforms have become an important part of the digital economy by facilitatingtransactions between large numbers of users and by fostering innovation on collaborativeplatforms. It is striking that platform-based services are dominated by a small number ofglobal players. Most of them are headquartered in the USA, including Alphabet, Amazon,Apple, Meta and Microsoft, also known as the "Big Five". A comparative analysis of the BigFive provides insights into their success factors and platform-related antitrust issues thatcould be helpful for policymakers to improve the European technology ecosystem. Businessdecision-makers can also benefit from these lessons learned when shaping digital strategies.
Keywords: L14; L22; L25; 330; online trade; digital platform; EU states; Online-Handel; Digitale Plattform; EU-Staaten